Demystifying the dark side of board political capital - Leung, Tak Yan; Sharma, Piyush (Elsevier, 2021)
Politically-connected directors help firms build ‘board political capital’ that may give them preferential access to benefits but it could also make them indulge in corrupt activities that in turn could lead to regulatory enforcement by authorities. However, it is still not clear which attributes of board political capital may expose firms to such negative outcomes. We address this gap by using an overarching dark side perspective of board political capital to hypothesize that regional (vs. central) board political capital, proportion of male (vs. female) politically-connected directors and perk consumption have positive effects on the incidence of regulatory enforcement. We also hypothesize that proximity to the regulatory authorities has a negative effect on regulatory enforcement and it negatively moderates the link between board political capital and regulatory enforcement. Data on 762 pairs of publicly listed Chinese firms supports most of the hypotheses. We discuss the theoretical and managerial implications of these results.